Chemical-mechanical coupling effects on the permeability of shale subjected to supercritical CO2-water exposure. (1st June 2022) - Yang, Kang; Zhou, Junping; Xian, Xuefu; Zhou, Lei; Zhang, Chengpeng; Tian, Shifeng; Lu, Zhaohui; Zhang, Fengshou
Abstract: The permeability of shale reservoir rock and caprock is the key parameters influencing the shale gas production and the storage security of CO2 . During the CO2 enhanced shale gas recovery, the issue of how the coupled chemical-mechanical process control the evolution of porosity and permeability in shale remains undetermined. In this study, multiple tests were conducted to obtained the shale properties alteration induced by ScCO2 -water exposure, including the mineral compositions measured by XRD, XRF and ICP-OES, the mechanical properties measured by uniaxial compression test, the pore structure and permeability of shale measured using nuclear magnetic resonance (NMR) at different confining stresses over a range of injection pressures. After ScCO2 -water exposure, the contents of carbonate and clay minerals decreased, while the contents of quartz and feldspar increased. The geochemical reaction altered the pore structure and mechanical properties of shale, resulting in the enlargement of pore, the decrease in uniaxial compressive strength and elastic modulus of shale, which in turn impact the porosity and permeability evolution in shale. At the unstressed state, the pore in shale was enlarged by the pure chemical reaction, leading to the increase in porosity and the initial permeability of shale. At the stressed condition, the porosity and permeability of shale is controlled by the chemical-mechanical coupling effects, the permeability of CO2 -water treated shale sample is lower than that of the untreated shale sample, which can be explained by the increase in stress sensitivity of shale permeability induced by the mechanical weakening, as the compressibility C f and permeability change rate Δ k c were increased after ScCO2 -water exposure. In addition, the stress sensitivity of permeability in shale is stress-dependent, for both untreated and ScCO2 -water treated shale samples, the C f and Δ k c of shale shown a negative relation with effective stress. At a higher effective stress condition, the change in the permeability of ScCO2 -water treated shale is more significantly enhanced. The results demonstrated that the ScCO2 -water-shale interaction induced chemical-mechanical effect may decrease the permeability of shale at in-situ stress condition, and hence adversely affecting the efficiency of gas recovery and CO2 sequestration in shale formation. Highlights: The influence of ScCO2 -water exposure on shale permeability at non-stressed and stressed conditions were investigated. The porosity and initial permeability of shale increased after ScCO2 -water exposure at non-stressed condition. The decrease in permeability of shale after ScCO2 -water exposure was observed under stress. The pore compressibility and stress sensitivity of permeability in shale increased after ScCO2 -water exposure. Permeability in shale are influenced by the combination of chemical-mechanical effects.